Essence and Content of the Competitiveness of the Officers of the National Police of Ukraine - E. Yu. Podorozhnii (Bulletin of Kharkiv National University of Internal Affairs)
It has been stated that the current Labor Code of Ukraine is outdated, the content of some of its provisions does not correspond to modern economic and social realities. Besides, a significant number of problematic issues remain unresolved, for example in regard to ensuring the guarantees of competitiveness of individual employees, in particular those who work in public authorities (in our case – law enforcement agencies), where one of the most important is certainly the National Police of Ukraine. It has been proved that competitiveness is a characteristic of the modern labor market. There are subjective and objective factors that affect the competitiveness of the profession of the National Police officer at the labor market.